The Role of Anger in Motivating Leadership - Heath, Iona; Stavdal, Anna; Sigurdsson, Johann Agust (Frontiers in Medicine, 2021)
As doctors, we see every working day the pervasive effects of different forms of structural violence and discrimination that undermine the hopes and aspirations of those on the losing side. This leads to powerlessness, fear and anger. Anger is not only forward facing but also directed toward, systems, institutions, governments—rather than individuals. At its best it is a protest against the status quo. We point out that leadership is one of the core values of our professionalism. In the light of what we see and hear, we have a responsibility to use the anger that this engenders within us to speak truth to power: this speaking is leadership. Our message is: feel the fear and the anger, use it to change the world, and enfold leadership in hope and the pursuit of justice.